2020
DOI: 10.1017/s1041610220000538
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of cognitive function and their determinants in older people: 12 years of follow-up in the Chinese Longitudinal Healthy Longevity Survey

Abstract: ABSTRACTBackground:Cognitive decline in advanced age is closely related to dementia. The trajectory of cognitive function in older Chinese is yet to be fully investigated. We aimed to investigate the trajectories of cognitive function in a nationally representative sample of older people living in China and to explore the potential determinants of these trajectories. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 48 publications
6
37
2
Order By: Relevance
“…There were three distinct trajectories of cognition, namely, persistently-high, medium-decrease, and low-increase. Compared with previous studies [21][22], similarly, the persistently-high class accounted for most of the population, indicating that majority of participants kept stable cognition through their aging periods. However, we also found an uncommon trajectory of low-increase, which was featured for low cognitive score in baseline and gradually improvement subsequently.…”
Section: Discussioncontrasting
confidence: 63%
“…There were three distinct trajectories of cognition, namely, persistently-high, medium-decrease, and low-increase. Compared with previous studies [21][22], similarly, the persistently-high class accounted for most of the population, indicating that majority of participants kept stable cognition through their aging periods. However, we also found an uncommon trajectory of low-increase, which was featured for low cognitive score in baseline and gradually improvement subsequently.…”
Section: Discussioncontrasting
confidence: 63%
“…The 2classes model were more popular in studies such as distinguishing AD converter vs. non-converter, and stable vs. decline [11,32,33]. The results revealed that stable-function class accounted for most of the population [5,34], indicating that majority of participants kept stable cognitive function through their aging periods.…”
Section: Discussionmentioning
confidence: 99%
“…Speci cally, leisure activities included housework, personal outdoor activities, garden work, reading newspapers or books, raising domestic animals or pets, playing cards or mahjong, watching TV or listening to the radio, and taking part in some social activities. According to previous study [5], each item had 5 levels and was coded as follows: "almost every day" (coded as 1), "not daily, but once a week" (coded as 2), "not weekly, but at least once a month" (coded as 3), "not monthly, but sometimes" (coded as 4), and "never" (coded as 5). The total scores of the above 8 items ranged 8-40.…”
Section: Measurement Of Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of risk factors and preventative strategies are primary objectives in research on impaired cognitive functioning in older adults (Brayne, 2007;Treichler and Jeste, 2019). Indeed, general health-related risk factors have been identified during midlife and old age (Launer, 2005;Launer, 2007;Kaufman and Perales-Puchalt, 2019;Lee et al, 2019;Shaaban et al, 2019;Tu et al, 2020;Walker et al, 2019). Nonetheless, a recent shift has seen studies that examine the role of early-life risk factors to increment current knowledge of risk factors (Grainger et al, 2019;Launer, 2007;Whalley et al, 2006;Williamson and Leroi, 2019).…”
Section: Introductionmentioning
confidence: 99%